2017
DOI: 10.1088/2058-6272/19/3/035101
|View full text |Cite
|
Sign up to set email alerts
|

Zonal flow energy ratio evolution during L-H and H-L transitions in EAST plasmas

Abstract: The essential role of zonal flow in the L-H transition and the suppression of turbulence have been studied with a long range correlation technique using Langmuir probe arrays in EAST tokamak. Two toroidally localized probe arrays are used to measure the zonal flow during L-H transition and H-L back transition. The energy ratio of the low frequency zonal flow to the total drift wave turbulence is calculated. During ELM-free H mode, the energy ratio is higher than that in L mode, which reveals the important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…The Co 3 O 4 /CNNS-1100 composite coupled with PMS was highly effective for TC remove within pH ≈2.0-10.0, wherein ≈99% TC was removed within 60 min reaction, which confirmed that the solution pH has minor effect on TC degradation. A mixture of anions such as Cl − , NO 3 − , HCO 3 − , and PO 4 3− might impact the pollutants removal ( Figure 6F). The listed anions exhibited the inhibition effect for TC degradation, while ≈95.7% TC still could be degraded by Co 3 O 4 /CNNS-1100 composite within 60 min.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Co 3 O 4 /CNNS-1100 composite coupled with PMS was highly effective for TC remove within pH ≈2.0-10.0, wherein ≈99% TC was removed within 60 min reaction, which confirmed that the solution pH has minor effect on TC degradation. A mixture of anions such as Cl − , NO 3 − , HCO 3 − , and PO 4 3− might impact the pollutants removal ( Figure 6F). The listed anions exhibited the inhibition effect for TC degradation, while ≈95.7% TC still could be degraded by Co 3 O 4 /CNNS-1100 composite within 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the anions may also trap radical, resulting in photocatalytic activity decrease. For example, it is known that the Cl − anion could quench the generated SO 4 •− to produce weaker radicals. [63] A previous report has indicated that, HCO 3 − usually acts as strong SO 4…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations